2018
DOI: 10.1101/456673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infectious Entry of Merkel Cell Polyomavirus

Abstract: 27Merkel Cell Polyomavirus (MCPyV) is a small, non-enveloped tumor virus associated 28 with an aggressive form of skin cancer, the Merkel cell carcinoma (MCC). MCPyV 29 infections are highly prevalent in the human population with MCPyV virions being 30 continuously shed from human skin. However, the precise host cell tropism(s) of 31MCPyV remains unclear: MCPyV is able to replicate within a subset of dermal 32fibroblasts, but MCPyV DNA has also been detected in a variety of other tissues. 33However, MCPyV appe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 112 publications
(167 reference statements)
1
27
0
Order By: Relevance
“…MCPyV PsVs transduced target cells more slowly than SV40 infection, with detectable fluorescence observed between 48 to 72 hours post-transduction (hpt), consistent with previously reported timescales (Fig. 1E-F) (25). Using these systems, SV40 infections and MCPyV transductions could be performed in a 96- or 24-well plate format, respectively, providing a platform for high-throughput antiviral compound screening.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…MCPyV PsVs transduced target cells more slowly than SV40 infection, with detectable fluorescence observed between 48 to 72 hours post-transduction (hpt), consistent with previously reported timescales (Fig. 1E-F) (25). Using these systems, SV40 infections and MCPyV transductions could be performed in a 96- or 24-well plate format, respectively, providing a platform for high-throughput antiviral compound screening.…”
Section: Resultssupporting
confidence: 90%
“…Following binding, JCPyV enters cells through clathrin-mediated endocytosis, whilst SV40, MCPyV and BKPyV enter via caveolar/lipid rafts (2227). virions traffic through the endosomal system and in response to endosomal cues, including endosome acidification, initiate proteolytic rearrangements of the capsid prior to retrograde trafficking to the endoplasmic reticulum (ER) (25, 2830). Within the ER, virions are further disassembled, exposing nuclear localisation signals (NLSs) that transport capsids to the nucleus via importins (3137).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been no cell lines available for the proliferation of HPyVs from clinical samples, with the exception of JCPyV and BKPyV [25]. Much of the research on polyomaviruses was performed using recombinant virions and pseudoviruses [26,27]. Previous studies showed that WUPyV-VP1 could be detected in cytokeratin + cells (epithelial cells), CD68 + cells (macrophage/monocyte lineage), and MUC5AC + cells (goblet cells) in the lung tissue by immunohistochemistry [11,28], indicating that WUPyV has obvious tropism for respiratory epithelia cells.…”
Section: Discussionmentioning
confidence: 99%
“…While there are significant commonalities between these viruses, they differ in their utilization of cellular receptors and entry routes for initiating infection. However, one distinct overlap in infection is clear: all polyomaviruses studied to date traffic to the endoplasmic reticulum following attachment and entry [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%